Foam, method for producing foam, and laminate

By using foam materials of specific structures of hydrogenated block copolymers and olefin resins in automotive interior materials, the problems of insufficient foam hardness and wear resistance are solved, and good appearance molding and comfortable cushioning performance are achieved, which is suitable for autonomous driving and shared travel environments.

JP2025018940APending Publication Date: 2025-02-06ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024092921
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-25
Filing Date
2024-06-07
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

The foam hardness and wear resistance of existing automotive interior materials cannot achieve good appearance molding and comfortable cushioning performance, and the wear resistance is insufficient, which cannot meet the needs of autonomous driving and shared travel.

Method used

Using foam materials containing hydrogenated block copolymers, olefin resins, thermoplastic resins and softeners, the thickness and expansion ratio of the foam core layer and the non-foam leather layer are optimized to form a foam structure with excellent wear resistance and appearance molding.

Benefits of technology

It achieves that foam materials have excellent wear resistance and durability while maintaining good appearance molding and comfortable cushioning performance, and are suitable for autonomous driving and shared travel environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018940000001_ABST
    Figure 2025018940000001_ABST
Patent Text Reader

Abstract

To provide a foam which has good molding appearance, cushioning property and abrasion resistance, and is also excellent in characteristic balance.SOLUTION: A foam of a hydrogenated block copolymer composition contains a hydrogenated block copolymer (a), an olefinic resin (b), a thermoplastic resin (c), and a softening agent (d), and has a foamed core layer and a non-foamed skin layer, wherein the foamed core layer has thickness of 300 μm or more and a foaming ratio of 1.2 times or more, a content of the polymer block (a) mainly containing a vinyl aromatic monomer unit in the hydrogenated block copolymer (a) is 10 to 40 mass%, the hydrogenated block copolymer (a) contains a hydrogenated copolymer block (b) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit, a content of the vinyl aromatic monomer unit in the hydrogenated block copolymer (b) is 5 to 79 mass%, and the hydrogenated block copolymer composition has a value of 15-second hardness measured by a durometer A according to JIS K 6253 of 85 or less and an MFR value of 40 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a foam, a method for producing a foam, and a laminate. [Background technology]

[0002] In recent years, autonomous driving and mobility services have been attracting attention as new directions for automobiles. This trend is also changing the performance required for automobile parts such as automobile interior materials. For example, it is expected that automobiles will become more meaningful as living spaces as autonomous driving advances. Therefore, interiors are becoming more luxurious and interior designs are becoming more diverse in order to create spaces where passengers can spend their time more comfortably. As a result, resin compositions that are used as materials for automobile interior materials are required to have a molded appearance that allows for more detailed designs and a foam hardness that allows for cushioning with a more comfortable feel than before. From the viewpoint of mobility services, it is believed that the spread of car sharing will lead to increased demand for longer life and cleanliness of automobiles. Therefore, automobile parts such as automobile interior materials will be cleaned more frequently than before, and the resin compositions used as materials will need to have higher abrasion resistance. Due to the spread of autonomous driving and mobility services as described above, in recent years, resin compositions are required to have better molded appearance, foam hardness, and excellent abrasion resistance than conventional products.

[0003] As materials for automobile parts, thermoplastic elastomer compositions containing a hydrogenated product of a block copolymer consisting of a conjugated diene compound and a vinyl aromatic compound, an olefin resin, and a softener, as well as foamed molded articles of the thermoplastic elastomer compositions have been proposed (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-98542 A [Patent Document 2] Special issue No. 2018-24822 [Patent Document 3] International Publication No. 2016 / 039310 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the foamed molded articles of the above-mentioned conventionally proposed thermoplastic elastomer compositions still have the problem that there is room for improvement in terms of the balance between the molded appearance, the foam hardness that provides comfortable cushioning properties, and the abrasion resistance.

[0006] Therefore, an object of the present invention is to provide a foam having a foamed core layer and a non-foamed skin layer, which has good molded appearance, cushioning properties and abrasion resistance, and which also has an excellent balance of these properties. [Means for solving the problem]

[0007] Means for Solving the Problems of the Prior Art As a result of intensive research conducted by the present inventors in order to solve the problems of the prior art described above, it has been found that, in a foam of a hydrogenated block copolymer composition containing a hydrogenated block copolymer, an olefin-based resin, a thermoplastic resin, and a softener, the foam has a foamed core layer and a non-foamed skin layer adjacent to each other, and by specifying the thickness of the foamed core layer constituting the foam, the expansion ratio, the structure of the hydrogenated block copolymer, the hardness of the hydrogenated block copolymer composition, and the MFR of the hydrogenated block copolymer composition within appropriate ranges, it is possible to provide a foam having a foamed core layer and a non-foamed skin layer which has good molded appearance, cushioning properties, and abrasion resistance of the foam surface, and which also has an excellent balance of these properties, thereby completing the present invention. That is, the present invention is as follows.

[0008] [1] A hydrogenated block copolymer (a), (b) an olefin resin; Thermoplastic resin (H), A softener (D); A foam of a hydrogenated block copolymer composition comprising: The foam has a foamed core layer and a non-foamed skin layer adjacent to each other, The foamed core layer has a thickness of 300 μm or more, The expansion ratio is 1.2 times or more, A foam that satisfies the following conditions (1) to (5). <Condition (1)>: The hydrogenated block copolymer (a) is a hydrogenated product of a block copolymer containing vinyl aromatic monomer units and conjugated diene monomer units. <Condition (2)>: The hydrogenated block copolymer (i) contains at least one polymer block (a) mainly composed of a vinyl aromatic monomer unit, The content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is from 10% by mass to 40% by mass. <Condition (3)>: The hydrogenated block copolymer (a) contains at least one hydrogenated copolymer block (b) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit, The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is from 5% by mass to 79% by mass. <Condition (4)>: The hydrogenated block copolymer composition has a 15-second hardness value of 85 or less as measured with a durometer type A in accordance with JIS K6253. <Condition (5)>: The hydrogenated block copolymer composition has an MFR value of 40 or more, measured according to JIS K7210 under conditions of a temperature of 230° C. and a load of 2.16 kg. [2] The foam according to [1] above, wherein the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 15% by mass or more and 79% by mass or less. [3] The hydrogenated block copolymer (a) is Contains at least one polymer block (a) mainly composed of vinyl aromatic monomer units, The foam according to [1] or [2], wherein the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is 15% by mass or more and 35% by mass or less. [4] The foam according to any one of [1] to [3] above, wherein the hydrogenated block copolymer composition has a 15-second hardness value measured with a durometer type A according to JIS K6253 of 30 or more and 75 or less. [5] The foam according to any one of [1] to [4] above, wherein the hydrogenated block copolymer composition has an MFR value of 100 or more and 1,000 or less, measured in accordance with JIS K7210 at a temperature of 230°C and a load of 2.16 kg. [6] The foam according to any one of the above [1] to [5], wherein the non-foamed skin layer has a thickness of 10 μm to 500 μm. [7] The foam according to any one of [1] to [6] above, wherein the foamed core layer has a thickness of 1000 μm to 20000 μm. [8] The foam according to any one of the above [1] to [7], wherein the olefin-based resin (ii) contains at least one kind of polypropylene-based resin. [9] The foam according to any one of [1] to [8] above, wherein the expansion ratio is 1.5 times or more.

[10] The foam according to any one of [1] to [9], which is a foam for an automobile part selected from the group consisting of a side molding, a grommet, a shift knob, a weather strip, a window frame and a sealing material therefor, an instrument panel, an assist grip, a handle, a shift lever, a console, an arm rest, a head rest, and a door panel.

[11] A method for producing the foam according to any one of [1] to

[10] above, a step of adding a blowing agent to the hydrogenated block copolymer composition, and injecting the mixture into a cavity formed in a mold of an injection molding machine, the cavity having a spatial volume adjustable by a movable core, to fill the cavity; a step of expanding a spatial volume of the cavity by the movable core to perform foam molding; having, A method for producing a foam.

[12] A layer having the foam according to any one of [1] to

[10] above; a layer having a base resin; A laminate having

[13] The laminate according to

[12] above, wherein the layer having the base resin and the layer having the foam are in direct contact with each other without an adhesive layer. Effect of the Invention

[0009] According to the present invention, a foam having a foamed core layer and a non-foamed skin layer can be obtained which has good molded appearance, cushioning properties and abrasion resistance, and which also has an excellent balance of these properties. [Brief description of the drawings]

[0010] [Figure 1] 1 shows a cross-sectional view of the laminate of Example 37. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment for carrying out the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content, and the present invention can be carried out in various modified forms within the scope of the gist of the present invention.

[0012] [Foam] The foam of this embodiment is A hydrogenated block copolymer (a), (b) an olefin resin; Thermoplastic resin (H), and a softener (iv). The foam of this embodiment has a foamed core layer and a non-foamed skin layer adjacent to each other, The foamed core layer has a thickness of 300 μm or more and an expansion ratio of 1.2 or more, and satisfies the following conditions (1) to (5). <Condition (1)>: The hydrogenated block copolymer (a) is a hydrogenated product of a block copolymer containing vinyl aromatic monomer units and conjugated diene monomer units. <Condition (2)>: The hydrogenated block copolymer (i) contains at least one polymer block (a) mainly composed of a vinyl aromatic monomer unit, The content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is from 10% by mass to 40% by mass. <Condition (3)>: The hydrogenated block copolymer (a) contains at least one hydrogenated copolymer block (b) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit, The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is from 5% by mass to 79% by mass. <Condition (4)>: The hydrogenated block copolymer composition has a 15-second hardness value of 85 or less as measured with a durometer type A in accordance with JIS K6253. <Condition (5)>: The hydrogenated block copolymer composition has an MFR value of 40 or more, measured according to JIS K7210 under conditions of a temperature of 230° C. and a load of 2.16 kg.

[0013] According to the above-mentioned constitution, a foam having a foamed core layer and a non-foamed skin layer can be obtained, which has good molded appearance, cushioning properties and abrasion resistance, and also has an excellent balance of these properties.

[0014] (Hydrogenated Block Copolymer Composition) The foam of the present embodiment is a foam of a hydrogenated block copolymer composition, and the hydrogenated block copolymer composition contains a hydrogenated block copolymer (a), an olefin resin (b), a thermoplastic resin (c), and a softener (d).

[0015] <Hydrogenated block copolymer (a)> The hydrogenated block copolymer (a) used in the foam of the present embodiment is a hydrogenated product of a block copolymer containing vinyl aromatic monomer units and conjugated diene monomer units (the above-mentioned condition (1)).

[0016] [Vinyl aromatic monomer unit] Examples of vinyl aromatic compounds that form vinyl aromatic monomer units include, but are not limited to, monomer units derived from styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, N,N-diethyl-p-aminoethylstyrene, and the like. In particular, styrene is preferred from the viewpoint of the balance between the cost and the mechanical strength of the hydrogenated block copolymer composition containing the hydrogenated block copolymer (a). These may be used alone or in combination of two or more.

[0017] [Conjugated diene monomer unit] A conjugated diene monomer unit is a monomer unit derived from a diolefin having a pair of conjugated double bonds. Examples of such diolefins include, but are not limited to, 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, and 1,3-hexadiene. In particular, 1,3-butadiene and isoprene are preferred from the viewpoint of a good balance between moldability and mechanical strength of the hydrogenated block copolymer composition. These may be used alone or in combination of two or more.

[0018] In this specification, in the composition of the hydrogenated block copolymer, the term "mainly composed of" means that the proportion in a specific block polymer or polymer block is 85 mass % or more, preferably 90 mass % or more, and more preferably 95 mass % or more. In addition, since the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 5% by mass or more and 79% by mass or less (the above-mentioned condition (3)), the polymer block (a) and the hydrogenated copolymer block (b) can be clearly distinguished from each other.

[0019] [Polymer block (a) mainly composed of vinyl aromatic monomer units] The hydrogenated block copolymer (a) used in the foam of this embodiment contains at least one polymer block (a) mainly composed of vinyl aromatic monomer units (condition (2) above). This tends to improve the blocking resistance of pellets of the hydrogenated block copolymer (a). In addition, the hydrogenated block copolymer (i) has a content of the polymer block (a) of 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. When the content of the polymer block (a) mainly composed of vinyl aromatic monomer units is 10 mass% or more, the blocking resistance of the pellets of the hydrogenated block copolymer (a) is good, and the foam of this embodiment exhibits excellent abrasion resistance and heat resistance.

[0020] If the hydrogenated block copolymer (A) pellets have good blocking resistance, blocking is less likely to occur even under conditions such as longer transportation times, higher loads, and severe temperature environments (e.g., areas with high outside temperatures and areas with large temperature differences), and this is expected to facilitate pellet measurement and blending during compound molding. In addition, the amount of anti-adhesive agent for the hydrogenated block copolymer (A) can be reduced, which is expected to have the effects of avoiding equipment contamination, reducing environmental load, and suppressing unexpected deterioration of physical properties, such as deterioration of transparency and mechanical strength. When the foam of the present embodiment shows good abrasion resistance, it can be used in applications requiring stricter abrasion resistance, such as automobile materials. For example, when used as a material for a molded body thinner than a general molded body or a more complicated / larger molded body in automobile interior materials, even when used for a longer period of time, the appearance of the material can be expected to be maintained comparable to that of the general molded body described above. In addition, when used in the automobile interior materials, when assuming a ride, even when subjected to friction by a higher load or a coarse fabric, such as jeans fabric, which is a fabric with a coarser texture than cotton fabric such as Kanakin No. 3, the appearance of the material can be expected to be maintained for a long period of time.

[0021] Furthermore, the hydrogenated block copolymer (i) has a content of polymer block (a) of 40% by mass or less, preferably 38% by mass or less, more preferably 36% by mass or less, and even more preferably 35% by mass or less. When the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is 40% by mass or less, the foam of the present embodiment tends to exhibit good heat resistance, and when it is 35% by mass or less, the foam tends to exhibit even better heat resistance.

[0022] The content of polymer block (a) in the hydrogenated block copolymer (i) can be measured by a method using a nuclear magnetic resonance (NMR) apparatus (the method described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981), hereinafter referred to as the "NMR method") using the block copolymer before hydrogenation and the hydrogenated block copolymer after hydrogenation as samples. The content of the polymer block (a) in the hydrogenated block copolymer (i) can be controlled within the above-mentioned numerical range mainly by adjusting the amount of the vinyl aromatic compound added to the polymerization reactor, the reaction temperature and the reaction time.

[0023] [Hydrogenated copolymer block (b)] The hydrogenated block copolymer (i) used in the foam of this embodiment contains at least one hydrogenated copolymer block (b) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit (the above-mentioned condition (3)). The content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b) is 5% by mass or more, preferably 15% by mass or more, more preferably 30% by mass or more, and even more preferably 45% by mass or more.

[0024] When the content of vinyl aromatic monomer unit in hydrogenated copolymer block (b) is 5% by mass or more, the foam of this embodiment exhibits good abrasion resistance.Furthermore, when the content is 15% by mass or more, higher abrasion resistance is exhibited, and it can be used in applications where abrasion resistance is more stringent, such as automobile interior materials, where a thinner molded body is required, or in automobile interior materials, where a higher load is assumed when riding in the vehicle, and friction is caused by coarse fabrics, such as jeans fabrics, which are coarser than cotton fabrics such as Kanakin No. 3, and where appearance must be maintained for a long time.

[0025] The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 79% by mass or less, preferably 75% by mass or less, and more preferably 70% by mass or less.

[0026] When the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 79 mass% or less, the foam of the present embodiment exhibits good heat resistance and can be used in applications where strict heat resistance is required, such as applications for making thinner molded articles in automobile interior materials, and applications where resistance is required to maintain the texture (grained texture) and shape (resistance to deformation due to heat) of the material for a long period of time when used for a long period of time or at higher temperatures.

[0027] The content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b) can be measured by a nuclear magnetic resonance (NMR) spectrometer or the like. The content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b) can be controlled within the above-mentioned numerical range by adjusting the amounts of the vinyl aromatic compound and conjugated diene added to the polymerization reactor, the reaction temperature, etc.

[0028] [Hydrogenated polymer block (c) mainly composed of conjugated diene monomer units] The hydrogenated block copolymer (i) used in the foam of this embodiment may contain one or more hydrogenated polymer blocks (c) mainly composed of conjugated diene monomer units (hereinafter, may be referred to as hydrogenated polymer block (c)). The hydrogenated block copolymer (A) containing the hydrogenated polymer block (C) tends to exhibit good abrasion resistance, scratch resistance, and low-temperature properties in the foam of the present embodiment. When the hydrogenated block copolymer (A) contains the hydrogenated polymer block (C), the compatibility of the hydrogenated block copolymer (A) with the polyolefin resin (B) and thermoplastic resin (C) described below is improved in the foam of the present embodiment, and the interfacial strength is further improved, and the abrasion resistance, scratch resistance, and low-temperature properties tend to be improved.

[0029] [Weight average molecular weight of hydrogenated block copolymer (a)] The hydrogenated block copolymer (a) used in the foam of the present embodiment has a weight average molecular weight (Mw) of preferably 20,000 or more, more preferably 30,000 or more, and even more preferably 50,000 or more, from the viewpoints of extrusion moldability during pellet production of the hydrogenated block copolymer (a) and of obtaining good mechanical strength in the foam of the present embodiment. The upper limit of the weight average molecular weight (Mw) is preferably not more than 300,000, more preferably not more than 200,000, and even more preferably not more than 150,000. When the weight average molecular weight (Mw) is not more than 300,000, the hydrogenated block copolymer (A) tends to be easily melted during pellet production (extrusion molding) of the hydrogenated block copolymer (A), resulting in stable strands and improved extrusion moldability. The weight average molecular weight of the hydrogenated block copolymer (a) of the present embodiment is determined by gel permeation chromatography (GPC) using a calibration curve (created using the peak molecular weight of the standard polystyrene) obtained by measuring commercially available standard polystyrene.

[0030] [Molecular weight distribution (Mw / Mn) of hydrogenated block copolymer (A)] The molecular weight distribution (Mw / Mn) of the hydrogenated block copolymer (A) used in the foam of the present embodiment is not particularly limited, but from the viewpoint of the moldability of the hydrogenated block copolymer (A), it is preferably 10 or less, more preferably 3 or less, and even more preferably 1.5 or less. From the viewpoint of the moldability of the hydrogenated block copolymer (A), the lower limit of Mw / Mn is preferably 1 or more, more preferably 1.005 or more, and even more preferably 1.01 or more. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the hydrogenated block copolymer (A) are measured by gel permeation chromatography (GPC), and the molecular weight of the peak of the chromatogram is determined using a calibration curve (created using the peak molecular weight of the standard polystyrene) obtained by measuring a commercially available standard polystyrene. The molecular weight distribution (Mw / Mn) of the hydrogenated block copolymer (A) is determined from the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn).

[0031] [Hydrogenation rate of double bonds of conjugated diene monomer units in hydrogenated block copolymer (a)] The hydrogenation rate of the double bonds of the conjugated diene monomer units in the hydrogenated block copolymer (i) used in the foam of this embodiment is preferably 20% or more, more preferably 50% or more, and even more preferably 92% or more, from the viewpoint of obtaining good weather resistance. In particular, in applications for automobile interiors, high abrasion resistance and weather resistance are required, so the hydrogenation rate tends to be preferably 92% or more. The hydrogenation rate of the double bonds of the conjugated diene monomer units in the hydrogenated block copolymer (A) can be controlled to the above-mentioned numerical range by adjusting the amount of hydrogenation. The hydrogenation rate can be measured by a nuclear magnetic resonance (NMR) spectrometer or the like.

[0032] [Structure of hydrogenated block copolymer (a)] The hydrogenated block copolymer (a) used in the foam of the present embodiment is not particularly limited, but examples thereof include those having a structure represented by the following general formula.

[0033] aba, (ab) n -X, c-(ba) n , c-(ab) n , c-(aba) n , c-(bab) n , c-(bca) n , a-(cbca) n , ac-(ba) n , ac-(ab) n , ac-(ba) n -b, ca-(ba) n -c,ac-(ba) n -c, ab-(ca) n -b, ac-(bc) n -ac, c-(abc) n -ac, a-(cb) n -ca, c-(ac) n -bcac, [(abc) n ] m -X, [a-(bc) n ] m -X, [(ab) n -c] m -X, [(aba) n -c] m -X, [(bab) n -c] m -X, [(cba) n ] m -X, [c-(ba) n ] m -X, [c-(aba) n ] m -X, [c-(bab) n ] m -X In each of the above general formulas, a represents a polymer block (a) mainly composed of vinyl aromatic monomer units, b represents a hydrogenated copolymer block (b) composed of vinyl aromatic monomer units and conjugated diene monomer units, and c represents a hydrogenated polymer block (c) mainly composed of conjugated diene monomer units. n is an integer of 1 or more, and preferably an integer of 1 to 5. m is an integer of 2 or more, and preferably an integer of 2-11. X represents a residue of a coupling agent or a residue of a multifunctional initiator.

[0034] The hydrogenated block copolymer (A) used in the foam of this embodiment may be a modified block copolymer to which an atomic group having a specific functional group is bonded. Since the presence or absence of a functional group has little effect on the hardness and / or MFR of the hydrogenated block copolymer (A), the presence or absence of modification of the hydrogenated block copolymer (A) and the type of the functional group may be appropriately determined according to the structure of the resin to be kneaded with the hydrogenated block copolymer (A). In addition, when the hydrogenated block copolymer (a) is used as a modified block copolymer, it may be a secondary modified block copolymer. In this specification, "secondary modification" is a name that is characterized by the manufacturing method, and the first step of bonding a functional group to a block copolymer is called primary modification, and the step of reacting the functional group with another compound is called secondary modification. For example, a typical method for manufacturing a secondary modified block copolymer is to react a modifier (e.g., amine) at the polymerization end terminal of the primary modified product after polymerization in a solution, with another compound (e.g., maleic acid) in an extruder to produce a secondary modified product.

[0035] <Method for producing hydrogenated block copolymer (a)> The hydrogenated block copolymer (a) used in the foam of the present embodiment, in the state before hydrogenation, can be obtained, for example, by carrying out living anionic polymerization of a vinyl aromatic compound and a conjugated diene compound in a hydrocarbon solvent using a polymerization initiator such as an organic alkali metal compound.

[0036] [Hydrocarbon solvents] Examples of hydrocarbon solvents include, but are not limited to, aliphatic hydrocarbons such as n-butane, isobutane, n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclohexane, cycloheptane, and methylcycloheptane; and aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene.

[0037] [Polymerization initiator] The polymerization initiator is not particularly limited, but examples thereof include organic alkali metal compounds such as aliphatic hydrocarbon alkali metal compounds, aromatic hydrocarbon alkali metal compounds, and organic amino alkali metal compounds, which are known to have anionic polymerization activity toward vinyl aromatic compounds and conjugated dienes. The organic alkali metal compound is not limited to the following, but for example, an aliphatic or aromatic hydrocarbon lithium compound having 1 to 20 carbon atoms is preferable, and a compound containing one lithium atom in one molecule, a dilithium compound containing multiple lithium atoms in one molecule, a trilithium compound, or a tetralithium compound can be used. Specific examples include n-propyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, n-pentyllithium, n-hexyllithium, benzyllithium, phenyllithium, tolyllithium, a reaction product of diisopropenylbenzene with sec-butyllithium, and a reaction product of divinylbenzene with sec-butyllithium and a small amount of 1,3-butadiene. Furthermore, for example, the organic alkali metal compounds disclosed in US Pat. No. 5,708,092, British Patent No. 2,241,239, and US Pat. No. 5,527,753 can also be used.

[0038] [Adjustment agent] When an organic alkali metal compound is used as a polymerization initiator to copolymerize a vinyl aromatic compound with a conjugated diene, the content of vinyl bonds (1,2-bonds or 3,4-bonds) resulting from the conjugated diene incorporated in the polymer and the random copolymerizability of the vinyl aromatic compound with the conjugated diene can be adjusted by using a specific regulator. Such regulators include, but are not limited to, tertiary amine compounds, ether compounds, metal alcoholate compounds, and the like. The regulator may be used alone or in combination of two or more kinds.

[0039] Examples of tertiary amine compounds include, but are not limited to, compounds represented by the general formula: R1R2R3N (wherein R1, R2, and R3 each represent a hydrocarbon group having 1 to 20 carbon atoms or a hydrocarbon group having a tertiary amino group). Specific examples include trimethylamine, triethylamine, tributylamine, N,N-dimethylaniline, N-ethylpiperidine, N-methylpyrrolidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, 1,2-dipiperidinoethane, trimethylaminoethylpiperazine, N,N,N',N",N"-pentamethylethylenetriamine, and N,N'-dioctyl-p-phenylenediamine.

[0040] The ether compound is not limited to the following, but examples thereof include linear ether compounds and cyclic ether compounds. Examples of linear ether compounds include, but are not limited to, dialkyl ether compounds of ethylene glycol, such as dimethyl ether, diethyl ether, diphenyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether, and dialkyl ether compounds of diethylene glycol, such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and diethylene glycol dibutyl ether. Examples of cyclic ether compounds include, but are not limited to, tetrahydrofuran, dioxane, 2,5-dimethyloxolane, 2,2,5,5-tetramethyloxolane, 2,2-bis(2-oxolanyl)propane, and alkyl ethers of furfuryl alcohol.

[0041] Examples of the metal alcoholate compound include, but are not limited to, sodium t-pentoxide, sodium t-butoxide, potassium t-pentoxide, potassium t-butoxide, and the like.

[0042] [Polymerization method] As a method for polymerizing a vinyl aromatic compound and a conjugated diene using an organic alkali metal compound as a polymerization initiator, a conventionally known method can be applied. Although not limited thereto, for example, any of batch polymerization, continuous polymerization, and a combination of these may be used, with batch polymerization being particularly suitable for obtaining a block copolymer having excellent heat resistance. The polymerization temperature is preferably from 0° C. to 180° C., more preferably from 30° C. to 150° C. The polymerization time varies depending on the conditions, but is usually within 48 hours, preferably from 0.1 to 10 hours. The polymerization atmosphere is preferably an inert gas atmosphere such as nitrogen gas. The polymerization pressure is not particularly limited as long as it is set within a pressure range that allows the monomer and the solvent to be maintained in a liquid phase within the above-mentioned temperature range. Furthermore, it is preferable to take care not to introduce impurities such as water, oxygen, carbon dioxide gas, etc., which may inactivate the catalyst and the living polymer, into the polymerization system.

[0043] Furthermore, at the end of the polymerization step, a required amount of a bifunctional or higher functional coupling agent may be added to carry out a coupling reaction. As the bifunctional coupling agent, known ones can be used, and examples thereof include, but are not limited to, alkoxysilane compounds such as trimethoxysilane, triethoxysilane, tetramethoxysilane, tetraethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane, dichlorodimethoxysilane, dichlorodiethoxysilane, trichloromethoxysilane, and trichloroethoxysilane; dihalogen compounds such as dichloroethane, dibromoethane, dimethyldichlorosilane, and dimethyldibromosilane; and acid esters such as methyl benzoate, ethyl benzoate, phenyl benzoate, and phthalic acid esters. As the polyfunctional coupling agent having three or more functionalities, conventionally known ones can be used, and are not particularly limited. For example, polyalcohols having three or more functionalities, epoxidized soybean oil, diglycidyl bisphenol A, 1,3-bis(N-N'-diglycidylaminomethyl)cyclohexane and other polyfunctional epoxy compounds; n (wherein R is a hydrocarbon group having 1 to 20 carbon atoms, X is a halogen, and n is an integer of 3 to 4), for example, methylsilyl trichloride, t-butylsilyl trichloride, silicon tetrachloride, and bromides thereof; n (wherein R is a hydrocarbon group having 1 to 20 carbon atoms, X is a halogen, and n is an integer of 3 to 4), for example, polyvalent halogen compounds such as methyltin trichloride, t-butyltin trichloride, and tin tetrachloride. Dimethyl carbonate, diethyl carbonate, and the like may also be used.

[0044] [Denaturation process] The hydrogenated block copolymer (a) used in the foam of this embodiment may be a modified block copolymer to which an atomic group having a functional group is bonded. The atomic group having a functional group is preferably bonded as a pre-step of the hydrogenation step described below. The "atomic group having a functional group" is not limited to the following, but examples thereof include atomic groups containing at least one functional group selected from hydroxyl group, carboxyl group, carbonyl group, thiocarbonyl group, acid halide group, acid anhydride group, carboxylic acid group, thiocarboxylic acid group, aldehyde group, thioaldehyde group, carboxylate group, amide group, sulfonic acid group, sulfonate group, phosphoric acid group, phosphoric acid ester group, amino group, imino group, nitrile group, pyridyl group, quinoline group, epoxy group, thioepoxy group, sulfide group, isocyanate group, isothiocyanate group, silicon halide group, silanol group, alkoxy silicon group, tin halide group, boronic acid group, boron-containing group, boronate base, alkoxy tin group, phenyl tin group, etc. In particular, atomic groups containing at least one functional group selected from hydroxyl group, epoxy group, amino group, silanol group, and alkoxy silane group are preferred. The "atomic group having a functional group" can be bonded by a modifying agent. Examples of the modifying agent include, but are not limited to, tetraglycidyl meta-xylylene diamine, tetraglycidyl-1,3-bisaminomethylcyclohexane, ε-caprolactone, δ-valerolactone, 4-methoxybenzophenone, γ-glycidoxyethyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl dimethylphenoxysilane, bis(γ-glycidoxypropyl)methylpropoxysilane, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, N,N'-dimethylpropylene urea, and N-methylpyrrolidone.

[0045] The modified block copolymer is not particularly limited, but can be obtained, for example, by anionic living polymerization using a polymerization initiator having a functional group or an unsaturated monomer having a functional group, forming a functional group at the living end, or by addition reaction of a modifying agent containing a functional group. Another method for obtaining a modified block copolymer includes reacting a block copolymer with an organic alkali metal compound such as an organolithium compound (metallation reaction), and then subjecting the block polymer to an addition reaction with a modifier having a functional group. However, in the latter method, a modified hydrogenated block copolymer can also be prepared by obtaining a hydrogenated block copolymer, subjecting the resulting copolymer to a metallation reaction, and then reacting the resulting copolymer with a modifying agent. The temperature at which the modification reaction is carried out is preferably 0 to 150° C., more preferably 20 to 120° C. The time required for the modification reaction differs depending on other conditions, but is preferably within 24 hours, more preferably 0.1 to 10 hours. Depending on the type of modifying agent used, the amino group etc. may generally be in the form of an organometallic salt at the stage of reacting with the modifying agent, in which case it can be converted to an amino group etc. by treating with a compound having active hydrogen such as water or alcohol. In such modified block copolymers, a part of the modified block copolymer may be mixed with a block copolymer that is not modified.

[0046] The modified block copolymer may be a secondary modified block copolymer, which is obtained by reacting the modified block copolymer with a secondary modifying agent having reactivity with the functional group of the modified block copolymer. The secondary modifying agent is not particularly limited, but examples thereof include a modifying agent having a functional group selected from the group consisting of a carboxyl group, an acid anhydride group, an isocyanate group, an epoxy group, a silanol group, and an alkoxysilane group, and has at least two functional groups selected from these functional groups. However, when the functional group is an acid anhydride group, the secondary modifying agent may have one acid anhydride group.

[0047] As described above, when the secondary modifier is reacted with the modified block copolymer, the amount of the secondary modifier used is preferably 0.3 to 10 mol, more preferably 0.4 to 5 mol, and even more preferably 0.5 to 4 mol, per equivalent of the functional group bonded to the modified block copolymer. The method of reacting the modified block copolymer with the secondary modifier can be any known method and is not particularly limited. For example, the melt-kneading method described below and the method of dissolving or dispersing and mixing each component in a solvent or the like and reacting them can be mentioned. It is preferable that these secondary modifications are carried out after the hydrogenation process of the block copolymer.

[0048] Suitable secondary modifying agents include, but are not limited to, maleic anhydride, pyromellitic anhydride, 1,2,4,5-benzenetetracarboxylic dianhydride, toluylene diisocyanate, tetraglycidyl-1,3-bisaminomethylcyclohexane, and bis-(3-triethoxysilylpropyl)-tetrasulfane.

[0049] The hydrogenated block copolymer (i) used in the foam of this embodiment may be a modified block copolymer graft-modified with an α,β-unsaturated carboxylic acid or a derivative thereof, such as an anhydride, ester, amide, or imide thereof. Examples of α,β-unsaturated carboxylic acids or derivatives thereof include, but are not limited to, maleic anhydride, maleic anhydride imide, acrylic acid or its ester, methacrylic acid or its ester, endo-cis-bicyclo[2,2,1]-5-heptene-2,3-dicarboxylic acid or its anhydride, and the like. The amount of the α,β-unsaturated carboxylic acid or a derivative thereof added is preferably from 0.01 to 20 parts by mass, and more preferably from 0.1 to 10 parts by mass, per 100 parts by mass of the hydrogenated block copolymer before modification. The reaction temperature in the case of graft modification is preferably from 100 to 300°C, more preferably from 120 to 280°C. The method for graft modification is not particularly limited, but for example, the method described in JP-A-62-79211 can be applied.

[0050] [Hydrogenation reaction process] The hydrogenated block copolymer (a) used in the foam of the present embodiment can be obtained by subjecting the above-mentioned non-hydrogenated unmodified or modified block copolymer to a hydrogenation reaction using a specific hydrogenation catalyst. Examples of the hydrogenation catalyst include, but are not limited to, known catalysts: (1) supported heterogeneous hydrogenation catalysts in which a metal such as Ni, Pt, Pd, Ru, etc. is supported on carbon, silica, alumina, diatomaceous earth, etc.; (2) so-called Ziegler-type hydrogenation catalysts which use a transition metal salt such as an organic acid salt or an acetylacetone salt of Ni, Co, Fe, Cr, etc., and a reducing agent such as organoaluminum; and (3) homogeneous hydrogenation catalysts such as so-called organometallic complexes of organometallic compounds such as Ti, Ru, Rh, Zr, etc. In addition, the hydrogenation catalyst is not limited to the following, but for example, hydrogenation catalysts described in JP-B-42-8704, JP-B-43-6636, JP-B-63-4841, JP-B-1-37970, JP-B-1-53851, and JP-B-2-9041 can also be used. Suitable hydrogenation catalysts include titanocene compounds, reducing organometallic compounds, or mixtures thereof. The titanocene compound is not limited to the following, but for example, the compounds described in JP-A-8-109219 can be used. Specific examples include compounds having at least one ligand having a (substituted) cyclopentadienyl skeleton, an indenyl skeleton, or a fluorenyl skeleton, such as biscyclopentadienyl titanium dichloride and monopentamethylcyclopentadienyl titanium trichloride. Examples of the reducing organometallic compound include, but are not limited to, organoalkali metal compounds such as organolithium compounds, organomagnesium compounds, organoaluminum compounds, organoboron compounds, and organozinc compounds.

[0051] The hydrogenation reaction will now be described. In general, the reaction temperature is preferably in the range of 0 to 200°C, more preferably in the range of 30 to 150°C. The pressure of hydrogen used in the hydrogenation reaction is preferably from 0.1 to 15 MPa, more preferably from 0.2 to 10 MPa, and even more preferably from 0.3 to 5 MPa. The hydrogenation reaction time is usually preferably 3 minutes to 10 hours, more preferably 10 minutes to 5 hours. The hydrogenation reaction may be a batch process, a continuous process, or a combination thereof. It is preferable to remove catalyst residues, if necessary, from the solution of the hydrogenated block copolymer obtained through the hydrogenation reaction, and separate the hydrogenated block copolymer from the solution. Examples of the separation method include, but are not limited to, a method in which a polar solvent that is a poor solvent for the hydrogenated modified copolymer, such as acetone or alcohol, is added to the reaction solution after hydrogenation to precipitate and recover the polymer; a method in which the reaction solution is poured into boiling water with stirring and the solvent is removed by steam stripping to recover the polymer; and a method in which the polymer solution is directly heated to distill off the solvent.

[0052] The hydrogenated block copolymer (a) used in the foam of this embodiment may contain various stabilizers such as phenol-based stabilizers, phosphorus-based stabilizers, sulfur-based stabilizers, and amine-based stabilizers.

[0053] <Olefin resin (ii)> The hydrogenated block copolymer composition constituting the foam of the present embodiment contains an olefin resin (b). The olefin-based resin (ii) used in the foam of this embodiment is not limited to the following, but examples thereof include homopolymers of α-olefins such as polyethylene (PE), polypropylene (PP), 1-butene, 1-pentene, 1-hexene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-octene, etc. Also included are random copolymers or block copolymers made of a combination of olefins selected from ethylene, propylene, butene, pentene, hexene, octene, etc. Specific examples of the copolymer include ethylene and / or propylene-α-olefin copolymers such as ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-3-methyl-1-butene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, ethylene-1-decene copolymer, propylene-1-butene copolymer, propylene-1-hexene copolymer, propylene-1-octene copolymer, propylene-4-methyl-1-pentene copolymer, ethylene-propylene-1-butene copolymer, propylene-1-hexene-ethylene copolymer, and propylene-1-octene-ethylene copolymer. The copolymers with ethylene and / or propylene also include copolymers with other unsaturated monomers other than the above α-olefins. Examples of the copolymers with other unsaturated monomers include, but are not limited to, copolymers of ethylene and / or propylene with unsaturated organic acids or derivatives thereof, such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, methyl acrylate, methyl methacrylate, maleic anhydride, arylmaleic imide, and alkylmaleic imide; copolymers of ethylene and / or propylene with vinyl esters, such as vinyl acetate; and copolymers of ethylene and / or propylene with non-conjugated dienes, such as dicyclopentadiene, 4-ethylidene-2-norbornene, 4-methyl-1,4-hexadiene, and 5-methyl-1,4-hexadiene. The (b) olefin-based resin preferably contains at least one type of polypropylene-based resin from the viewpoints of economy and of obtaining high transparency by achieving good compatibility with other components in the hydrogenated block copolymer composition constituting the foam of the present embodiment.

[0054] The olefin resin (ii) may be modified with a predetermined functional group. The functional group is not particularly limited, but examples thereof include an epoxy group, a carboxy group, an acid anhydride group, and a hydroxyl group. The functional group-containing compound or modifier for modifying the olefin resin (ii) is not particularly limited, but includes the following compounds. Examples of the unsaturated epoxides include glycidyl methacrylate, glycidyl acrylate, vinyl glycidyl ether, and allyl glycidyl ether, and unsaturated organic acids include maleic acid, fumaric acid, itaconic acid, citraconic acid, allyl succinic acid, maleic anhydride, fumaric anhydride, and itaconic anhydride, etc. In addition, although not particularly limited, examples of the unsaturated epoxides include ionomers and chlorinated polyolefins.

[0055] The olefin-based resin (b) is preferably a polypropylene-based resin such as a polypropylene homopolymer or an ethylene-propylene random or block copolymer, from the viewpoints of economy and of obtaining good compatibility in the hydrogenated block copolymer composition constituting the foam of the present embodiment and thus high transparency. In particular, from the viewpoints of transparency and flexibility, ethylene-propylene random copolymers are more preferable. The olefin resin (ii) may be composed of only one type of material, or may be composed of two or more types in combination.

[0056] <(C) Thermoplastic resin> The hydrogenated block copolymer composition constituting the foam of the present embodiment contains a thermoplastic resin (iii). Examples of the thermoplastic resin (iii) include, but are not limited to, block copolymers of conjugated diene compounds and vinyl aromatic compounds and hydrogenated products thereof (however, different from the hydrogenated block copolymer (iii) of the present embodiment described above), polymers of the vinyl aromatic compounds, copolymers of the vinyl aromatic compounds and other vinyl monomers, for example, ethylene, propylene, butylene, vinyl chloride, vinylidene chloride, vinyl acetate, acrylic acid, acrylic acid esters such as methyl acrylate, methacrylic acid esters such as methyl methacrylate, acrylonitrile, methacrylonitrile, etc., rubber-modified styrene-based resins (HIPS), acrylonitrile-butadiene-styrene copolymer resins (ABS), methacrylic acid ester-butadiene-styrene copolymer resins (MBS), and the like.

[0057] Examples of the thermoplastic resin (c) include polymers of acrylic acid and its esters and amides, polyacrylate resins, polymers of acrylonitrile and / or methacrylonitrile, nitrile resins which are copolymers of these acrylonitrile monomers with other copolymerizable monomers containing 50% by mass or more of these acrylonitrile monomers, polyamide resins such as nylon-46, nylon-6, nylon-66, nylon-610, nylon-11, nylon-12, and nylon-6 / nylon-12 copolymers, polyester resins, thermoplastic polyurethane resins, poly-4,4'-dioxydiphenyl-2,2'-propanecaprolactone, and the like. Examples of the polycarbonate-based polymer include polycarbonate-based polymers, thermoplastic polysulfones such as polyethersulfone and polyallylsulfone, polyoxymethylene-based resins, polyphenylene ether-based resins such as poly(2,6-dimethyl-1,4-phenylene) ether, polyphenylene sulfide-based resins such as polyphenylene sulfide and poly4,4'-diphenylene sulfide, polyarylate-based resins, polyether ketone polymers or copolymers, polyketone-based resins, fluorine-based resins, polyoxybenzoyl-based polymers, polyimide-based resins, and polybutadiene-based resins such as 1,2-polybutadiene and trans-polybutadiene.

[0058] As the thermoplastic resin (iii), polystyrene, styrene resins such as rubber-modified styrene resins, polyamide resins, polyester resins, and polycarbonate resins are particularly preferred. The number average molecular weight of the thermoplastic resin (iii) is generally 1000 or more, preferably 5000 to 5 million, and more preferably 10,000 to 1 million.

[0059] <(D) Softener> The hydrogenated block copolymer composition constituting the foam of the present embodiment contains a softener (iv). The softener (iv) is preferably a rubber softener which softens the hydrogenated block copolymer composition and imparts flowability and processability to the composition. Examples of rubber softeners include, but are not limited to, mineral oils and liquid or low molecular weight synthetic softeners. Among these, naphthenic and / or paraffinic process oils or extender oils are preferred. Mineral oil-based rubber softeners are mixtures of aromatic rings, naphthenic rings, and paraffin chains; those in which the carbon number of the paraffin chains accounts for 50% or more of the total carbon are called paraffinic, those in which the carbon number of the naphthenic rings accounts for 30-45% are called naphthenic, and those in which the aromatic carbon number exceeds 30% are called aromatic. A synthetic softener may be used in the hydrogenated block copolymer composition of the present embodiment, and examples of the synthetic softener include, but are not limited to, polybutene, low molecular weight polybutadiene, liquid paraffin, etc. (d) As the softener, the mineral oil-based rubber softeners are more preferable.

[0060] When high heat resistance and mechanical properties are required for the hydrogenated block copolymer composition constituting the foam of the present embodiment, the mineral oil-based rubber softener used preferably has a kinetic viscosity at 40°C of 60 cst or more, more preferably 120 cst or more. The softener (iv) may be used alone or in combination of two or more kinds.

[0061] <Contents of Components (A) to (D) in the Hydrogenated Block Copolymer Composition> The contents of the components (a) to (d) in the hydrogenated block copolymer composition constituting the foam of the present embodiment are described below. The content of the hydrogenated block copolymer (i) is preferably from 3% by mass to 95% by mass, more preferably from 5% by mass to 70% by mass, even more preferably from 7% by mass to 60% by mass, and even more preferably from 9% by mass to 50% by mass. When the content of the hydrogenated block copolymer (A) in the hydrogenated block copolymer composition is within the above range, the bubbles tend to be fine and highly independent during foam molding, leading to high foamability, which tends to improve heat insulation and provide excellent long-term bubble stability, moldability, and abrasion resistance. The content of the olefin resin (ii) is preferably 1% by mass or more and 42% by mass or less, more preferably 3% by mass or more and 38% by mass or less, even more preferably 6% by mass or more and 34% by mass or less, and even more preferably 10% by mass or more and 30% by mass or less. When the content of the olefin resin (b) is within the above range, the balance of foamability, flexibility and heat resistance tends to be good. The content of the thermoplastic resin (iii) is preferably from 1 mass% to 60 mass%, more preferably from 3 mass% to 50 mass%, even more preferably from 6 mass% to 40 mass%, and even more preferably from 10 mass% to 30 mass%. When the content of the thermoplastic resin (iii) is within the above range, the balance of foamability, flexibility, moldability and toughness tends to be good. The content of the softener (iv) is preferably from 1% by mass to 65% by mass, more preferably from 5% by mass to 60% by mass, even more preferably from 10% by mass to 55% by mass, and even more preferably from 20% by mass to 50% by mass. When the content of the softener (d) is within the above range, the balance between foamability, flexibility and moldability tends to be good.

[0062] <Additives> The hydrogenated block copolymer composition constituting the foam of the present embodiment may contain any additives, if necessary, in addition to the components (a), (b), (c), and (d). There are no particular limitations on the type of additive, so long as it is one that is generally used in compounding thermoplastic resins or rubber-like polymers.

[0063] The additives are not particularly limited as long as they are generally used in compounding thermoplastic resins or rubber-like polymers, such as fillers, lubricants, release agents, plasticizers, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, flame retardants, antistatic agents, reinforcing agents, and colorants.

[0064] Examples of fillers include, but are not limited to, inorganic fillers such as silica, talc, mica, calcium silicate, hydrotalcite, kaolin, diatomaceous earth, graphite, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, calcium sulfate, and barium sulfate, and organic fillers such as carbon black. Examples of lubricants include, but are not limited to, stearic acid, behenic acid, zinc stearate, calcium stearate, magnesium stearate, ethylene bisstearamide, and the like. Examples of the plasticizer include, but are not limited to, organic polysiloxanes and mineral oils. The antioxidant includes, but is not limited to, a hindered phenol-based antioxidant. Examples of the heat stabilizer include, but are not limited to, phosphorus-based, sulfur-based and amine-based heat stabilizers. Examples of light stabilizers include, but are not limited to, hindered amine light stabilizers. Examples of the ultraviolet absorbing agent include, but are not limited to, benzotriazole-based ultraviolet absorbing agents. Examples of reinforcing agents include, but are not limited to, organic fibers, glass fibers, carbon fibers, and metal whiskers. Examples of colorants include, but are not limited to, titanium oxide, iron oxide, and carbon black. Other examples include those listed in "Rubber and Plastic Compounding Chemicals" (compiled by Rubber Digest Co., Ltd.).

[0065] (Method for Producing Hydrogenated Block Copolymer Composition) The hydrogenated block copolymer composition constituting the foam of the present embodiment can be produced by a conventionally known method. The method for producing the hydrogenated block copolymer composition of this embodiment is not limited to the following, but examples thereof include a method of melt-kneading each component (the hydrogenated block copolymer (a), the polyolefin resin (b), the thermoplastic resin (c), the softener (d), and other additives as necessary) using a mixer such as a Banbury mixer, a single screw extruder, a twin screw extruder, a co-kneader, or a multi-screw extruder, and a method of dissolving or dispersing and mixing each component using a solvent and then removing the solvent by heating. In particular, the melt kneading method using an extruder is preferable from the viewpoints of productivity and good kneading properties. The shape of the hydrogenated block copolymer composition is not limited to the following, and may be any shape, such as pellets, sheets, strands, chips, etc. After melt-kneading, a molded article may be produced directly.

[0066] (Hardness of Hydrogenated Block Copolymer Composition) The hydrogenated block copolymer composition constituting the foam of the present embodiment has a 15-second hardness value measured with a durometer type A according to JIS K6253 of 85 or less, preferably 80 or less, more preferably 75 or less, and even more preferably 70 or less. When the hydrogenated block copolymer composition constituting the foam of the present embodiment has an instantaneous hardness of 85 or less as measured with a durometer type A according to JIS K6253, the foam of the present embodiment has an extremely good cushioning feel and a soft touch.

[0067] The hydrogenated block copolymer composition constituting the foam of the present embodiment preferably has a 15-second hardness value measured with a durometer type A according to JIS K6253 of 30 or more, more preferably 35 or more, and even more preferably 40 or more. This tends to result in good blocking resistance in pellets of the hydrogenated block copolymer composition. If the pellets of the hydrogenated block copolymer composition have high blocking resistance, blocking is less likely to occur during transportation for a longer period of time, under higher loads, and in severe temperature environments, such as in areas with high outside temperatures or areas with large temperature differences, and this is expected to facilitate pellet measurement and blending during compound molding, etc. In addition, since the amount of anti-blocking agent added can be reduced, it is possible to avoid equipment contamination and reduce the environmental load, and it is expected to suppress unexpected deterioration of physical properties, such as a decrease in transparency and mechanical strength.

[0068] The hardness of the hydrogenated block copolymer composition can be controlled within the above-mentioned numerical range by adjusting the hardness of the hydrogenated block copolymer (A) contained in the hydrogenated block copolymer composition, the hardness of component (C) in the hydrogenated block copolymer composition, the flexural modulus of component (B), the viscosity of component (D), and the composition ratio of components (A) to (D). The hardness of the hydrogenated block copolymer (a) can be controlled by appropriately adjusting the weight average molecular weight of the hydrogenated block copolymer (a), the content of polymer block (a) in the hydrogenated block copolymer composition, the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b), the content of hydrogenated polymer block (c), the amount of vinyl bonds in the conjugated diene monomer units of the hydrogenated block copolymer (a), the hydrogenation rate of double bonds in the conjugated diene monomer units of the hydrogenated block copolymer (a), etc. Furthermore, the hardness of the hydrogenated block copolymer (i) may be controlled by adjusting the tan δ peak temperature (loss tangent) from −25° C. to 60° C. in the viscoelasticity measurement chart of the hydrogenated block copolymer (i), i.e., the glass transition temperature derived from the hydrogenated copolymer block (b), through the polymerization reaction using a predetermined regulator that adjusts the vinyl bond amount in the hydrogenated copolymer block (b), the content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b), and the copolymerizability between the vinyl aromatic compound and the conjugated diene.

[0069] (MFR of hydrogenated block copolymer composition) The hydrogenated block copolymer composition constituting the foam of the present embodiment has an MFR of 40 or more, preferably 60 or more, and more preferably 100 or more, measured according to JIS K7210 at a temperature of 230°C and a load of 2.16 kg. When the hydrogenated block copolymer composition constituting the foam of the present embodiment has an MFR of 40 or more, the foam tends to exhibit good processability. When the processability of the hydrogenated block copolymer composition constituting the foam of this embodiment is good, a foam with an extremely thin layer can be molded, and in particular, a foam with a thin non-foamed skin layer can be obtained. In addition, in foam molding, stripes, pockmarks, and swirl marks such as flow marks are unlikely to occur, and a foam with good surface appearance can be obtained. In addition, molding using a more complicated mold or a mold with a smaller thickness becomes possible, and weight reduction by thinning can be achieved. Furthermore, higher processability tends to be advantageous for improving surface appearance, molding using a complicated mold, and thinning. Furthermore, the higher the processability, the more the amount of processing aids such as the softener (iv) in the hydrogenated block copolymer composition can be reduced, which tends to increase the freedom in the blending amount and improve the mechanical strength and tactile feel of the hydrogenated block copolymer composition, thereby resulting in a reduction in the environmental load.

[0070] The upper limit of the MFR of the hydrogenated block copolymer composition constituting the foam of the present embodiment is preferably 2000 or less, more preferably 1000 or less, and even more preferably 500 or less, from the viewpoint of maintaining heat resistance.

[0071] The MFR of the hydrogenated block copolymer composition can be controlled within the above-mentioned numerical range by adjusting the MFRs of components (a), (b), and (c) in the hydrogenated block copolymer composition, the viscosity of component (d), and the composition ratio of components (a) to (d). The MFR of the hydrogenated block copolymer (i) can be controlled by adjusting the weight average molecular weight, the content of polymer block (a), the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b), the content of hydrogenated polymer block (c), the amount of vinyl bonds in the conjugated diene monomer units of the hydrogenated block copolymer (i) before hydrogenation, and the hydrogenation rate of the double bonds in the conjugated diene monomer units of the hydrogenated block copolymer (i). For example, the MFR of the hydrogenated block copolymer (a) tends to be improved by a decrease in the weight average molecular weight of the hydrogenated block copolymer (a), a decrease in the content of polymer block (a), an increase in the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b), an increase in the content of hydrogenated polymer block (c) in the terminal blocks, a decrease in the content of hydrogenated polymer block (c) in the internal blocks, an increase in the amount of vinyl bonds in the conjugated diene monomer units, and a decrease in the hydrogenation rate of double bonds in the conjugated diene monomer units. In particular, the weight average molecular weight of the hydrogenated block copolymer (a) has a linear relationship with the logarithm of MFR. Therefore, in order to exhibit the blocking resistance of the hydrogenated block copolymer composition pellets and the heat resistance and abrasion resistance of the hydrogenated block copolymer composition, the content of the polymer block (a) in the hydrogenated block copolymer (a) and the content of the vinyl aromatic monomer unit in the hydrogenated copolymer block (b) are adjusted, and then the weight average molecular weight that gives the desired MFR can be determined from the linear relationship between the weight average molecular weight of the hydrogenated block copolymer (a) and the logarithm of MFR.

[0072] [Method for producing foam] The method for producing a foam of the present embodiment includes the steps of adding a blowing agent (e) to the hydrogenated block copolymer composition, injecting the composition into a cavity formed in a mold of an injection molding machine, the cavity having a spatial volume that can be adjusted by a movable core, and filling the cavity with the composition, and expanding the spatial volume of the cavity by the movable core, thereby performing foam molding. Specifically, the hydrogenated block copolymer composition is injected into a cavity space formed in a mold, and immediately thereafter or after a predetermined time has elapsed, the movable die or a movable core provided in the movable die is pulled back to a predetermined position at a predetermined rate, and the hydrogenated block copolymer composition expands in the cavity space, thereby performing foam molding.

[0073] There are chemical and physical foaming methods. In either method, a chemical foaming agent such as an inorganic foaming agent or an organic foaming agent, or a physical foaming agent is added, and the foaming agent is volatilized and / or decomposed by heating or the like to distribute bubbles inside the hydrogenated block copolymer composition. The foam of this embodiment can be manufactured, for example, by core-back injection molding, and is characterized in that the non-foamed skin layer and the foamed core layer are integrally molded, and the foamed core layer and the non-foamed skin layer are adjacent to each other. Core-back injection molding is effective in reducing the number of molding steps, since the foamed core layer, which has cushioning properties, and the non-foamed skin layer, which has design properties and is harder than the foamed core layer, can be molded in the same process. A counter pressure device may also be used to remove swirl marks on the surface of the foam.

[0074] (Foaming agent (e)) As the foaming agent (e), an inorganic foaming agent, an organic foaming agent, or a physical foaming agent can be used. Examples of inorganic foaming agents include, but are not limited to, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate, ammonium nitrite, azide compounds, sodium borohydride, aluminum acetate, metal powder, and the like. Examples of organic blowing agents include, but are not limited to, azodicarbonamide, azobisformamide, azobisisobutyronitrile, barium azodicarboxylate, N,N'-dinitrosopentamethylenetetramine, N,N'-dinitroso-N,N'-dimethylterephthalamide, benzenesulfonyl hydrazide, p-toluenesulfonyl hydrazide, p,p'-oxybisbenzenesulfonyl hydrazide, p-toluenesulfonyl semicarbazide, and the like. Examples of physical blowing agents include, but are not limited to, hydrocarbons such as pentane, butane, and hexane; halogenated hydrocarbons such as methyl chloride and methylene chloride; gases such as nitrogen, carbon dioxide, and air; and fluorinated hydrocarbons such as trichlorofluoromethane, dichlorodifluoromethane, trichlorotrifluoroethane, chlorodifluoroethane, and hydrofluorocarbons. Moreover, these foaming agents (e) may be used in combination. The blending amount of the foaming agent (e) is preferably from 0.1 to 30 parts by mass, more preferably from 2 to 25 parts by mass, and further preferably from 3 to 20 parts by mass, based on 100 parts by mass of the hydrogenated block copolymer composition.

[0075] (foaming aid) In the step of preparing the foam, a foaming assistant may be used together with the foaming agent (e) described above. The foaming assistant is not particularly limited, and any foaming assistant that has been conventionally and widely used can be used. Examples of the zinc compounds include urea compounds, zinc oxide, zinc stearate, zinc benzenesulfinate, zinc toluenesulfonate, zinc trifluoromethanesulfonate, zinc carbonate, and other zinc compounds, lead dioxide, and lead tribasic compounds. When the foaming agent (e) and the foaming assistant are used in combination, the blending amount of the foaming assistant is preferably 0.1 to 1000 parts by mass, more preferably 0.5 to 500 parts by mass, and further preferably 1 to 200 parts by mass, per 100 parts by mass of the foaming agent.

[0076] (Foam nucleating agent) In the step of producing the foam, a foam nucleating agent may be used. The foam nucleating agent is not particularly limited, and any agent that has been conventionally used as a foam nucleating agent can be used. Examples include titanium oxide, talc, kaolin, clay, calcium silicate, silica, sodium citrate, calcium carbonate, diatomaceous earth, calcined perlite, zeolite, bentonite, glass, limestone, calcium sulfate, aluminum oxide, titanium oxide, magnesium carbonate, sodium carbonate, ferric carbonate, and polytetrafluoroethylene powder. The amount of the foaming nucleating agent is preferably 0.01 to 100 parts by mass, more preferably 0.05 to 50 parts by mass, and even more preferably 0.1 to 10 parts by mass, per 100 parts by mass of the hydrogenated block copolymer composition.

[0077] [Structure of foam] The foam of this embodiment can be produced by core-back injection molding as described above. The foam of this embodiment has a structure in which a non-foamed skin layer and a foamed core layer are integrally molded, and the foamed core layer having cushioning properties and the non-foamed skin layer having harderness than the foamed core layer are adjacent to each other.

[0078] (Expansion Ratio) The foam of this embodiment has an expansion ratio of 1.2 times or more, preferably 1.5 times or more, more preferably 1.7 times or more, even more preferably 1.9 times or more, and even more preferably 2 times or more. When the foaming ratio is 1.2 times or more, excellent cushioning feeling and excellent appearance can be obtained. The expansion ratio of the foam can be calculated by dividing the thickness (mm) of the foamed core layer of the foam after core-back injection molding by the thickness (mm) of the void portion of the cavity when the cavity in the mold of the injection molding machine is filled with the hydrogenated block copolymer composition. The expansion ratio of the foam can be controlled within the above-mentioned range by adjusting the types and compositions of the components (A) to (D) in the hydrogenated block copolymer composition, the type and added amount of the blowing agent (E), the filling amount of the hydrogenated block copolymer composition, and the molding temperature and pressure in the molding step in the production process of the foam. In particular, in the case of core-back injection molding, the above-mentioned numerical ranges can be controlled by appropriately adjusting the types and compositions of the components (a) to (d) in the hydrogenated block copolymer composition, the type of blowing agent (e), the filling amount of the hydrogenated block copolymer composition, the opening degree of the core-back, the amount added, the temperature of the hydrogenated block copolymer composition to be injected, the temperature of the mold (fixed part / movable part), the injection speed, the injection pressure, the delay time from after filling to the start of the core-back, the number of core-back stages and the opening degree and core-back speed at each stage, the cooling time, and the shape of the mold in the foam production process.

[0079] (Non-foamed skin layer) The foam of this embodiment has a configuration in which a foamed core layer and a non-foamed skin layer are adjacent to each other. The thickness of the non-foamed skin layer is preferably 10 μm to 1000 μm, more preferably 10 μm to 700 μm, and even more preferably 10 μm to 500 μm, from the viewpoint of obtaining a good cushioning feel and a molded appearance. When the foam of this embodiment is produced by core-back injection molding, the thickness of the non-foamed skin layer can be controlled to within the above numerical range by appropriately adjusting the types and compositions of the components (a) to (d) in the hydrogenated block copolymer composition, the type of foaming agent (e), the filling amount of the hydrogenated block copolymer composition, the opening degree of the core-back, the amount added, the temperature of the injected resin, the temperature of the mold (fixed part / movable part), the injection speed, the injection pressure, the delay time from after filling to the start of core-back, the number of core-back stages and the opening degree and core-back speed at each stage, the cooling time, and the shape of the mold in the foam production process.

[0080] (foam core layer) The foam of this embodiment has a configuration in which a foamed core layer and a non-foamed skin layer are adjacent to each other. From the viewpoint of obtaining a good cushioning feeling, the thickness of the foamed core layer is 300 μm or more, preferably 700 μm or more, and more preferably 1000 μm or more. The upper limit of the thickness of the foamed core layer is not particularly limited, but is preferably 20000 μm or less. In the case of core-back injection molding, in order to obtain a good molded appearance (without flow marks, swirl marks, pockmarks, or sink marks), the thickness of the foamed core layer can be controlled within the above numerical range by appropriately adjusting the types and compositions of components (a) to (d) in the hydrogenated block copolymer composition, the type of foaming agent (e), the filling amount of the hydrogenated block copolymer composition, the opening degree of the core-back, the amount added, the temperature of the injected resin, the temperature of the mold (fixed part / movable part), the injection speed, the injection pressure, the delay time from after filling to the start of core-back, the number of core-back stages and the opening degree and core-back speed at each stage, the cooling time, and the shape of the mold in the foam production process.

[0081] [Uses of foam] The foam of the present embodiment can be used, for example, for automobile parts, food packaging materials, medical instruments, home appliance parts, electronic device parts, building materials, industrial parts, household goods, toy materials, footwear materials, fiber materials, and the like. Examples of automotive parts include, but are not limited to, side moldings, grommets, shift knobs, weather strips, window frames and their sealants, instrument panels, assist grips, handles, shift levers, consoles, armrests, headrests, and door panels. Examples of medical devices include, but are not limited to, medical tubes, medical hoses, catheters, blood bags, infusion bags, platelet storage bags, and artificial dialysis bags. Examples of building materials include, but are not limited to, wall materials, floor materials, and the like. Other examples include, but are not limited to, industrial hoses, food hoses, vacuum cleaner hoses, electrical cooling packing, various covering materials for electrical wires and the like, covering materials for grips, soft dolls, and the like. The foam of the present embodiment may be appropriately subjected to processing such as foaming, powdering, stretching, bonding, printing, painting, plating, and the like.

[0082] [Laminate] The laminate of the present embodiment has a layer having the foam of the present embodiment and a layer having a base resin. Examples of the base resin include, but are not limited to, polypropylene, polyethylene, polymethyl methacrylate, polyacrylonitrile, polymethacrylonitrile rubber modified styrene resin (HIPS), acrylonitrile-butadiene-styrene copolymer resin (ABS), and methacrylate-butadiene-styrene copolymer resin (MBS). As the base resin, polypropylene and ABS resin are particularly preferred from the viewpoint of imparting good rigidity to the laminate of the present embodiment. The layer having the foam may be composed only of the foam of this embodiment, or may be a laminate with a layer of another material. The layer having the base resin may be composed only of the base resin, may be a laminate of the above-mentioned base resin and another resin, or may be composed of a mixed resin of the above-mentioned base resin and another resin. An example of a method for laminating a layer having a foam and a layer having a base resin is a method in which, after injection molding of the base resin, the hydrogenated block copolymer composition of the present embodiment is subjected to core-back injection molding by two-color molding. As a result, the layer having the base resin and the layer having a foam exhibit good adhesion, and a laminate can be obtained without an adhesive layer, making it possible to reduce the molding process of the laminate and improve recyclability. As described above, the laminate of this embodiment may be configured such that the layer having the base resin and the layer having the foam are in direct contact with each other without an adhesive layer, or may be configured such that the layers are laminated together via a specified adhesive layer. EXAMPLES

[0083] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples and comparative examples. The methods for measuring and evaluating physical properties used in the examples and comparative examples are shown below.

[0084] The hydrogenated block copolymers used in the foams of the Examples and Comparative Examples were subjected to structural identification and physical property measurement as described below.

[0085] [Method of measuring the structure of hydrogenated block copolymer] ((1) Content of total vinyl aromatic monomer units (styrene) in hydrogenated block copolymer (A)) The hydrogenated block copolymer was used to measure the total vinyl aromatic monomer unit (styrene) content using an ultraviolet spectrophotometer (Shimadzu Corporation, UV-2450).

[0086] ((2) Hydrogenation rate of double bonds of conjugated diene monomer units of hydrogenated block copolymer (a)) The hydrogenation rate of the double bonds of the conjugated diene monomer units was measured using the hydrogenated block copolymer with a nuclear magnetic resonance spectrometer (ECS400, manufactured by JEOL RESONANCE).

[0087] ((3) Content of polymer block (a) in hydrogenated block copolymer (a)) The content of the polymer block (a) mainly composed of vinyl aromatic monomer units was measured using a hydrogenated block copolymer by a nuclear magnetic resonance (NMR) apparatus (the method described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981). Hereinafter, this method will be referred to as the "NMR method").

[0088] ((4) Content of hydrogenated copolymer block (b) in hydrogenated block copolymer (a)) Calculated using the formula: 100 - (content of hydrogenated copolymer block (a) in hydrogenated block copolymer (a)).

[0089] ((5) Amount of vinyl bonds in hydrogenated block copolymer (a)) The amount of vinyl bonds in hydrogenated block copolymers was measured by nuclear magnetic resonance (NMR). The amount of vinyl bonds in the conjugated diene monomer units in the hydrogenated block copolymer was determined from the ratio of the total peak area of ​​1,2-bonds and 3,4-bonds to the total area of ​​all peaks related to the conjugated diene monomer units (the ratio of 1,2-bonds, 3,4-bonds, and 1,4-bonds) among the peaks obtained by NMR measurement.

[0090] ((6) Content of vinyl aromatic monomer units in hydrogenated copolymer block (b) constituting hydrogenated block copolymer (a)) The vinyl aromatic monomer unit content in the hydrogenated copolymer block (b) relative to the entire polymer was calculated from the difference between the total vinyl aromatic monomer unit content in the hydrogenated block copolymer (a) measured in (1) above and the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (a) measured in (3) above, and the vinyl aromatic monomer unit content in the hydrogenated copolymer block (b) was calculated from the ratio to the content of the hydrogenated copolymer block (b) in the hydrogenated block copolymer (a) measured in (4) above.

[0091] [Method of measuring physical properties of hydrogenated block copolymer] ((1) Hardness) According to JIS K6253, the values ​​at 15 seconds were measured using a durometer type A and a durometer type D. The hardness value was measured 15 seconds after the probe of the hardness tester was lowered onto the measurement sample. In the following Tables 1 and 2, the hardness is indicated as "JIS-A, 15 seconds" and the hardness is indicated as "JIS-D, 15 seconds," respectively. Regarding the hardness value, when durometer type D indicates a hardness value of less than 20, the value of durometer type A is used, and when durometer type A indicates a hardness value of more than 90, the value of durometer type D is used. As a guideline, a hardness of 94 on durometer type A corresponds to a hardness of 45 on durometer type D.

[0092] ((2) Melt flow rate (MFR, unit: g / 10 min) The MFR was measured at a temperature of 230° C. and a load of 2.16 kg in accordance with JIS K7210.

[0093] [Method of measuring physical properties of hydrogenated block copolymer composition] The hydrogenated block copolymer compositions used in the foams of the Examples and Comparative Examples were subjected to physical property measurements as follows.

[0094] ((1) Hardness) According to JIS K6253, the value at 15 seconds was measured using a durometer type A. The hardness value was measured 15 seconds after the probe of the hardness tester was lowered onto the measurement sample. In the following Tables 3 to 12, hardness is indicated as (JIS-A, 15s).

[0095] ((2)MFR) The MFR was measured at a temperature of 230° C. and a load of 2.16 kg in accordance with JIS K7210.

[0096] [Measurement of physical properties and evaluation of characteristics of foam] The foams of the examples and comparative examples were subjected to measurement of physical properties and evaluation of characteristics as described below.

[0097] ((1) Foaming ratio) The thickness (mm) of the foamed core layer of the foam after core-back injection molding was calculated by dividing it by the thickness (mm) of the void portion of the cavity when the hydrogenated block copolymer composition was filled into the cavity in the mold of the injection molding machine.

[0098] ((2) Measurement of the thickness of the non-foamed skin layer) The foam was cut in the thickness direction perpendicular to the injection surface, and the cross section was observed under an optical microscope. The thickness of the skin layer on the observation surface was measured.

[0099] ((3) Measurement of foam core layer thickness) The foam was cut in the thickness direction perpendicular to the injection surface, and the cross section was observed under an optical microscope. The thickness of the core layer on the observation surface was measured.

[0100] ((4) Abrasion resistance of foam surface) Using a Gakushin type friction tester (AB-301 model, manufactured by Tester Sangyo Co., Ltd.), the leather-embossed surface of the foam obtained by the core-back injection molding was rubbed with a friction cloth, Kanakin No. 3 cotton, and a load of 1000 g, and the abrasion resistance was evaluated based on the mass loss after rubbing, according to the following criteria. <Evaluation criteria> 4: After 1000 friction cycles, the mass loss is less than 50 mg 3: After 1000 friction cycles, the mass loss is 50 mg or more and less than 150 mg. 2: After 1000 friction cycles, the mass loss is 150 mg or more and less than 250 mg. 1: After 1000 friction cycles, the mass loss is 250 mg or more.

[0101] In terms of abrasion resistance, a score of 2 or more is considered to be acceptable, and is evaluated as being excellent in terms of improved durability when thinner / complex molded bodies are used, when abraded by higher loads or coarse fabrics, and improved freedom of formulation. If the abrasion resistance is good, it can be used in applications that require stricter abrasion resistance, such as in automotive materials. For example, in automotive interior materials, even when molding thinner walls or more complex / larger molded bodies, it is comparable to small, general molded bodies with simple shapes, and the appearance of the material can be expected to be maintained even when used for a long period of time. In addition, when the hydrogenated block copolymer composition is used as an automobile interior material, assuming that the vehicle is being driven, the appearance of the material can be expected to be maintained for a long period of time even when it is subjected to abrasion caused by a higher load or a coarser fabric (for example, jeans fabric, which is a coarser fabric than cotton fabric such as Kanakin No. 3).

[0102] ((5) Surface appearance of foam) The foam obtained by injection molding the hydrogenated block copolymer composition was checked for the presence of flow marks, pockmarks (lost air bubbles), swirl marks, uneven transfer of grains and the like due to the molding die, sink marks, and the like. The appearance was rated as follows: 3 points for no practical problems, 2 points for slight defects that may cause practical problems, and 1 point for noticeable defects that may cause practical problems. A score of 2 or above was considered a pass.

[0103] ((6) Cushioning properties of foam Five examiners measured whether the foam sinks when pressed with a finger. The cushioning was rated according to the following criteria: strong cushioning was given a score of 3, medium cushioning was given a score of 2, and none was given a score of 1. <Evaluation criteria> 5: Total score is 15 points 4: Total score is 12-14 points 3: Total score is 9-11 points 2: Total score is 6-8 points 1: Total score is 5 points

[0104] A score of 2 or more was considered to be a pass, and the foam was evaluated as having cushioning properties.

[0105] [Foam] The foam was produced using a hydrogenated block copolymer (a), an olefin resin (b), a thermoplastic resin (c), and a softener (d), which will be described later.

[0106] (Production of hydrogenated block copolymer (a)) <Preparation of hydrogenation catalyst> In the examples and comparative examples described later, the hydrogenation catalyst used in producing the hydrogenated block copolymer was prepared by the following method. A reaction vessel equipped with a stirrer was purged with nitrogen and charged with 1 liter of dried and purified cyclohexane. Next, 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added. While thoroughly stirring the mixture, an n-hexane solution containing 200 mmol of trimethylaluminum was added and the mixture was allowed to react at room temperature for about 3 days to obtain a hydrogenation catalyst.

[0107] <Production Example 1: Hydrogenated Block Copolymer (a)-1> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 15 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.107 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.9 mol of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as "TMEDA") per 1 mol of n-butyllithium were added and polymerized at 65°C for 1 hour. Next, a cyclohexane solution (concentration 20% by mass) containing 29 parts by mass of butadiene and 41 parts by mass of styrene was added and polymerized for 2 hours at 80° C. Finally, a cyclohexane solution (concentration 20% by mass) containing 15 parts by mass of styrene was added and polymerized for 1 hour at 65° C. Thereafter, methanol was added to terminate the polymerization reaction. The block copolymer obtained as described above had a styrene content of 71% by mass, a polystyrene block content of 30% by mass, a vinyl bond amount of 22% by mass, and a weight average molecular weight of 60,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting block copolymer in an amount of 100 ppm (Ti standard) per 100 parts by mass of the block copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 65°C. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the block copolymer to obtain a hydrogenated block copolymer (a)-1. The hydrogenation rate of the resulting hydrogenated block copolymer (a)-1 was 98%. Other physical properties are shown in Table 1.

[0108] <Production Examples 2 to 16: Hydrogenated Block Copolymers (A)-2 to 13, (A)-A to C> In the method for producing the hydrogenated block copolymer (a)-1, the polymerization method and hydrogenation conditions were adjusted to produce (a)-2 to 13 and (a)-A to C. The physical properties of these copolymers are shown in Tables 1 and 2 below.

[0109] [Production of hydrogenated block copolymer composition] Hydrogenated block copolymer compositions were produced using the above-mentioned hydrogenated block copolymers (a)-1 to (a)-13 and (a)-A to C and the following components (b) to (d).

[0110] (Olefin Resin (ii)) <Component (b)-1> Olefin resin: Polypropylene resin, PM801A (manufactured by SunAllomer Co., Ltd.) <Component (b)-2> Olefin resin: Polypropylene resin, PLB00A (manufactured by SunAllomer Co., Ltd.) <Component (b)-3> Olefin resin: Polypropylene resin, PL500A (manufactured by SunAllomer Co., Ltd.)

[0111] (Thermoplastic resin (H)) <Component (H)-1> Thermoplastic resin: styrene-based thermoplastic elastomer, N504 (manufactured by Japan Elastomer Co., Ltd.) <Component (H)-2> Thermoplastic resin: styrene-based thermoplastic elastomer Content of polymer block (a): 35% by mass; content of hydrogenated copolymer block (b): 65% by mass; content of vinyl aromatic compound in hydrogenated copolymer block (b): 21% by mass; average molecular weight: 250,000; vinyl bond amount: 35% by mass; hydrogenation rate: 98% by mass

[0112] (Softener (D)) <Ingredients (D)> Softener: Paraffin oil, PW-90 (Idemitsu Kosan)

[0113] [Production of hydrogenated block copolymer composition and foam] Example 1 <Production of Hydrogenated Block Copolymer Composition> The hydrogenated block copolymer (a)-1 in pellet form, the olefin resin (b), the thermoplastic resin (c), and the softener (d) were blended in the ratios (parts by mass) shown in Table 3 below, kneaded in a twin-screw extruder (TEX-30), and pelletized to obtain a hydrogenated block copolymer composition. The extrusion conditions were a cylinder temperature of 230° C. and a screw rotation speed of 300 rpm. The resulting hydrogenated block copolymer composition was injection molded at 210° C. to prepare an injection-molded sheet having a thickness of 2 mm, and a specimen for measuring physical properties was obtained. The results of the physical property measurements are shown in Table 3.

[0114] (Examples 2 to 36, Comparative Examples 1 to 7) <Production of Hydrogenated Block Copolymer Composition> Hydrogenated block copolymer compositions were produced in the same manner as in Example 1 above, except that the components were changed as shown in Tables 3 to 12, and the physical properties thereof were measured. The results of the physical property measurements are shown in Tables 3 to 12.

[0115] (Production of foams of Examples 1 to 36 and Comparative Examples 1 to 7) To pellets of the hydrogenated block copolymer composition prepared based on the blending ratios (parts by mass) shown in Tables 3 to 12, 4 to 6 parts by mass of a sodium bicarbonate-based foaming agent Polythrene: EE-25C (manufactured by Eiwa Chemical Industry Co., Ltd.) was externally added as a foaming agent (e) per 100 parts by mass of the hydrogenated block copolymer composition, and dry blended. A dry blend of the hydrogenated block copolymer composition pellets and the foaming agent was molded into a 30 x 40 cm flat plate using an injection molding machine with a core-back function (MD450S manufactured by UBE Machinery Co., Ltd.) Half of the plate was given a leather grain finish. The mixture was injected into a mold with a thickness of 0.5 to 3.5 mm at a nozzle temperature of 220°C, mold temperature (fixed part 40°C, movable part 35°C) and injection speed of 100 mm / s using a full shot method, then the mold was cored back at 480 mm / s to allow the mixture to expand to a desired expansion ratio, and cooled for 20 seconds to form the desired foam. The foam has a structure of a non-foamed skin layer / foamed core layer / non-foamed skin layer adjacent to each other.

[0116] The following Tables 1 and 2 show the physical properties of the hydrogenated block copolymer (a), and Tables 3 to 12 show the physical properties of the hydrogenated block copolymer composition, and the physical properties and characteristic evaluation results of the foam.

[0117]

Table 1

[0118]

Table 2

[0119]

Table 3

[0120]

Table 4

[0121]

Table 5

[0122]

Table 6

[0123]

Table 7

[0124]

Table 8

[0125]

Table 9

[0126]

Table 10

[0127]

Table 11

[0128] [Table 12]

[0129] It was found that the foam of the present invention has good molded appearance, cushioning properties, and abrasion resistance, and also has an excellent balance of these properties.

[0130] [Production of Laminate] (Example 37) A 1.8 mm PP (polypropylene) substrate was injection molded at a nozzle temperature of 220° C. and a mold temperature of 40° C. Then, in the same manner as above, hydrogenated block copolymer composition (a)-1 was laminated by core-back foam molding in two-color molding to obtain a laminate in which a foam made of the hydrogenated block copolymer composition was laminated on the PP substrate. A cross-sectional view of the laminate is shown in FIG. The foam layer made of the hydrogenated block copolymer composition had an original thickness of 2 mm before foaming and a thickness of 3.9 mm after foaming, the non-foamed skin layer on the side not in contact with the PP base material was 300 μm thick, the non-foamed skin layer on the side in contact with the PP base material was 150 μm thick, and the foamed core layer was 3,450 μm thick. The obtained laminate was found to have good molded appearance, abrasion resistance, cushioning properties, and good rigidity. [Industrial Applicability]

[0131] The foam of the present invention has industrial applicability in the fields of automobile parts (automobile interior materials, automobile exterior materials), medical device materials, various containers such as food packaging containers, home appliances, industrial parts, toys, and the like.

Claims

1. A hydrogenated block copolymer (a), (b) an olefin resin; Thermoplastic resin (c), A softener (D); A foam of a hydrogenated block copolymer composition comprising: The foam has a foamed core layer and a non-foamed skin layer adjacent to each other, The foam core layer has a thickness of 300 μm or more, The expansion ratio is 1.2 times or more, A foam satisfying the following conditions (1) to (5): <Condition (1)>: The hydrogenated block copolymer (a) is a hydrogenated product of a block copolymer containing vinyl aromatic monomer units and conjugated diene monomer units. <Condition (2)>: The hydrogenated block copolymer (a) contains at least one polymer block (a) mainly composed of a vinyl aromatic monomer unit, The content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is from 10% by mass to 40% by mass. <Condition (3)>: The hydrogenated block copolymer (a) contains at least one hydrogenated copolymer block (b) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit, The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is from 5% by mass to 79% by mass. <Condition (4)>: The hydrogenated block copolymer composition has a 15-second hardness value of 85 or less as measured with a durometer type A in accordance with JIS K6253. <Condition (5)>: The hydrogenated block copolymer composition has an MFR value of 40 or more, measured in accordance with JIS K7210 under conditions of a temperature of 230° C. and a load of 2.16 kg.

2. The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 15% by mass or more and 79% by mass or less.

2. The foam of claim 1.

3. The hydrogenated block copolymer (a) is Contains at least one polymer block (a) mainly composed of vinyl aromatic monomer units, the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (i) is 15% by mass or more and 35% by mass or less; 2. The foam of claim 1.

4. The hydrogenated block copolymer composition has a 15-second hardness value measured with a durometer type A in accordance with JIS K6253 of 30 or more and 75 or less.

2. The foam of claim 1.

5. The hydrogenated block copolymer composition has an MFR value of 100 or more and 1,000 or less, measured in accordance with JIS K7210 under conditions of a temperature of 230° C. and a load of 2.16 kg.

2. The foam of claim 1.

6. The non-foamed skin layer has a thickness of 10 μm to 500 μm.

2. The foam of claim 1.

7. The foam core layer has a thickness of 1000 μm to 20000 μm.

2. The foam of claim 1.

8. The olefin-based resin (ii) contains at least one polypropylene-based resin, 2. The foam of claim 1.

9. The foam according to claim 1 , wherein the expansion ratio is 1.5 times or more.

10. The foam is a foam for automotive parts, selected from the group consisting of side moldings, grommets, shift knobs, weather strips, window frames and their sealants, instrument panels, assist grips, handles, shift levers, consoles, arm rests, head rests, and door panels.

2. The foam of claim 1.

11. A method for producing the foam according to any one of claims 1 to 10, comprising the steps of: a step of adding a blowing agent to the hydrogenated block copolymer composition, and injecting the mixture into a cavity formed in a mold of an injection molding machine, the cavity having a spatial volume adjustable by a movable core, to fill the cavity; a step of expanding a spatial volume of the cavity by the movable core to perform foam molding; having, A method for producing a foam.

12. A layer comprising the foam according to any one of claims 1 to 10; a layer having a base resin; A laminate having

13. the layer having the base resin and the layer having the foam are in direct contact with each other without an adhesive layer; The laminate according to claim 12.

Citation Information

Patent Citations

  • Thermoplastic elastomer composition

    JP2015098542A

  • Thermoplastic elastomer composition and molded article of same

    WO2016039310A1